INFLUENCE OF ZINC OXIDE NANOPARTICLES ON BILAYER LIPID MEMBRANE PROPERTIES - Torosyan, A.L.; Ananyan, G.V.; Arakelyan, V.B. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
The effect of zinc oxide nanoparticles ( ZnO ) on the stability and conductivity of the bilayer lipid membrane (BLM) in solution was studied. It has been shown that ZnO nanoparticles increase the stability of BLM in an electric field, and BLM becomes more stable with increasing their concentration. The increase in the stability of BLM in an electrical field is mainly due to the increase in the coefficient of linear tension of the pore edge, which is forming in BLM. It is also shown, that the presence of ZnO nanoparticles in the solution surrounding BLM leads to a decrease in the BLM conductivity.